2012
DOI: 10.1557/jmr.2012.314
|View full text |Cite
|
Sign up to set email alerts
|

Combinatorial search of structural transitions: Systematic investigation of morphotropic phase boundaries in chemically substituted BiFeO3

Abstract: We review our work on combinatorial search and investigation of morphotropic phase boundaries (MPBs) in chemically substituted BiFeO 3 (BFO). Utilizing the thin-film composition spread technique, we discovered that rare-earth (RE 5 Sm, Gd, and Dy) substitution into the A-site of the BFO lattice results in a structural phase transition from the rhombohedral to the orthorhombic phase. At the structural boundary, both the piezoelectric coefficient and the dielectric constant are substantially enhanced. It is also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
1
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 60 publications
2
32
1
3
Order By: Relevance
“…Interestingly, a new mode at 310 cm −1 derived from orthorhombic structure gradually became apparent from x = 0.12–0.16 in the Raman spectrum. The coexistence of A 1 modes and the 310 cm −1 mode in the range of x = 0.12–0.16 further substantiated the formation of MPB . For easy identification, the multiple Raman peaks of the sample at x = 0.16 were fitted through Lorentzian function, as revealed in Figure c, from which both the A 1 modes and the 310 cm −1 mode were labeled.…”
Section: Resultsmentioning
confidence: 67%
“…Interestingly, a new mode at 310 cm −1 derived from orthorhombic structure gradually became apparent from x = 0.12–0.16 in the Raman spectrum. The coexistence of A 1 modes and the 310 cm −1 mode in the range of x = 0.12–0.16 further substantiated the formation of MPB . For easy identification, the multiple Raman peaks of the sample at x = 0.16 were fitted through Lorentzian function, as revealed in Figure c, from which both the A 1 modes and the 310 cm −1 mode were labeled.…”
Section: Resultsmentioning
confidence: 67%
“…We have previously shown that Pearson is effective as one metric for carrying out clustering of Raman spectroscopy data. 34 We are currently in the process of evaluating different metrics for a variety of data formats from other materials characterization techniques.…”
Section: Existing Problems and Future Workmentioning
confidence: 99%
“…Many of the algorithms developed for handling large amount of XRD data are also applicable to rapid analysis of other spectra such as Raman, XPS, and FTIR data. 408 As a general comment, computational combinatorial approaches have recently received much attention with the arrival of the Materials Genome Initiative (MGI). 409 To take advantage of the power of high-throughput methodologies, an integrated strategy combining computational methods with rapid experimental verification work is required.…”
Section: High-throughput Mapping Of Phase Diagramsmentioning
confidence: 99%